Impact of radiation exposure on mechanical and superconducting properties of Bi-2212 superconductor ceramics - Rahman A.A.; Hamid N.A.; Asbullah M.S.N. (Institute of Physics Publishing, 2023)
In the last few years, rapid improvements have been made to improve the quality of high-temperature superconductors. Amongst the high temperature superconductors, the Bi-based (BSCCO) consists of interest for various applications. Bi2Sr2CaCu2O8 (Bi-2212) have been used to make superconducting tapes and wires. Unlike conventional compound superconductors, the critical current, Ic of oxide superconducting tapes in the elastic strain is generally almost constant and degrades suddenly when it is subject to mechanical force by a strain beyond the limit. In this research, the Bi-2212 samples were prepared by solid state reaction method. Precursors oxide powders were pressed to pallets under hydrostatic pressure around 7 tons or 70 000 psi and then sintered at temperature of 850C for 24 hours. The effect of radiation before and after irradiation on mechanical and superconducting properties of the samples was studied. Irradiation was carried out with a beam of 3 MeV, current of 10 mA and radiation dose of 100 and 200 KGray. The x-ray diffraction analysis is used to verify Bi-2212 phase. The samples were also characterized through electrical properties by using the four-point probe method. The microstructure of the samples was studied by using the scanning electron microscopy (SEM), and compression test was also conducted using the stress-strain relationship. The phase structure and electrical properties of the samples degrade slightly with irradiation exposure. Nevertheless the microstructure showed that when initial electron radiation dose was increased up to 100 kGray, the grain growth, texture and core density improved slightly but the grain growth, size and core density begin to deteriorate after the electron radiation dose is increased to 200 kGray. This may be due to the formation of larger size defects within the microstructure of the Bi-2212 phase as the radiation dose increases. Published under licence by IOP Publishing Ltd.